A survey analysis on abandoned housing projects in Malaysia. The house buyers’ perspectives - Haron, Razali; Abdul Razak, Dzuljastri; Babatunde, Jaiyeoba Haruna (2015)
The House Buyer Association (HBA), representing house buyers in Malaysia believe that purchasing and ultimately owning a house is everyone’s biggest dream and brings a sense of accomplishment and pride to one’s life. However, it is not uncommon that house buyers encounter problems in the process of owning a house, where their dream house projects were abandoned. The Ministry of Housing and Local Government’s regards abandoned housing projects as a highly serious problem that demands urgent attention. As of May, 2015 alone, Malaysia records a huge number of 17,987 families being affected from 157 abandoned housing projects. Realising the dire needs to mitigate this abandoned housing projects, this study aims to provide insights into this matter through a survey analysis carried out among 328 house buyers covering 11 states in Malaysia. Using Likert scale, the analysis revealed that lack of enforcement of housing law and policy as one of the main contributing factors of abandoned housing projects and the house buyers are not adequately protected under the existing law and practices. The developers and the banks have taken advantage of the Sell Then Build (STB) system where associated risks were being transferred to the house buyers through progressive payments and the monthly installments. The study provides insights to practitioners and policy makers on further improvements of the law and policy to mitigate or prevent abandoned housing projects as well as to protect house buyers’ interests in the case of late delivery or even if their dream house project is unfortunately abandoned.